Incorporation of eribulin in the systemic treatment of metastatic breast cancer patients in Australia. Issue 3 (14th April 2021) - Chan, Arlene; Lomma, Christopher; Chih, HuiJun; Blackely, Elizabeth; Woodward, Natasha; Tsoi, Daphne; Cheong, Kerry; Chipman, Mitchell; Redfern, Andrew
Abstract: Purpose: Review of utilization and efficacy of eribulin in Australian metastatic breast cancer (MBC) patients. Methods: Retrospective review of consecutive MBC patients treated with eribulin in tertiary Australian BC centers. Key inclusion criteria included eribulin administration in nonclinical trial setting from October 2014 onwards, known duration of MBC systemic treatments administered and known follow‐up date after eribulin. Cox regression model was used to assess survival. Results: Study population comprised 266 patients from eight centers treated between October 2014 and May 2018. Median age at time of MBC diagnosis was 54 years with 18% of patients having de novo MBC. Seventy‐six percent had hormone receptor positive (HRp) disease, 19% triple negative (TN) and 5% HER2‐positive. CNS involvement was present in 36% of patients. Eribulin was most frequently given as third‐line chemotherapy (36%), with no prior anthracycline exposure in 14% of total population. Eribulin was given more frequently as ≤third‐line chemotherapy than > third‐line in patients with TN disease, ≥ two metastatic sites or CNS disease. Median overall survival (OS) from eribulin administration was 9.2 (95% CI [8.0, 10.3]) months. Conclusion: Similar efficacy was demonstrated for eribulin when given in the first‐line to beyond the fifth line of chemotherapy in all subtypes of MBC. Abstract : Similar efficacy was demonstrated for eribulin when given in the first‐line to beyond the fifth line of chemotherapy in all subtypes of MBC. There was no significant OS advantage when eribulin was given ≤ third‐line compared to > third‐line chemotherapy (adjusted HR 0.99; 95% CI [0.75, 1.29])